An Investigation of the Interaction between Melittin and a Model Lipid Bilayer - Slyngborg, Morten; Skovsen, Esben; Fojan, Peter (Journal of Self Assembly and Molecular Electronics, 2023)
The recent emergence of multi-drug resistant bacteria has rendered many common antibiotics ineffective and therefor novel drugs are needed. Antimi- crobial peptides have proven applicable in this aspect as they can form self-assembled pore structures in the lipid bilayer of bacterial cells. The exact pore formation is shrouded in controversy and largely unknown as it is difficult to determine empirically. The development of coarse grain force fields in molecular dynamic simulations enables longer timescales and extended simulation systems. This allows for the simulation of lipid bilayer self- assembly and bilayer-antimicrobial peptide interactions. The present work focuses on the antimicrobial peptide, melittin, induced pore formation and is aimed towards determining the mechanism and pore structure